(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the evolution of recitative-declamatory forms in Kazakh opera from the 1930s through the early twenty-first century. It analyzes the organic fusion of epic oral-poetic folklore with European classical operatic conventions in seminal works such as E. G. Brusilovsky’s Er Targyn (1937), A. Zhubanov & L. Khamidi’s Abay (1944), G. Zhubanova’s Englik-Kebek (1958), and Zheruyik (1985). Employing music-analytical, historical-stylistic, and comparative methodologies, the study explores modal, melodic-rhythmic, and genre-specific features of recitative, supported by score examples and archival audio recordings. In Er Targyn, the use of Phrygian mode, repetitive intonations, and shifting tempi underscores the epic narrative. In Abay, the three-part arioso of the elder Sırttan utilizes contrasting modes, orchestral textures, and tempo changes to deepen emotional impact. The analysis of Englik-Kebek reveals melodic variants of terme, dombra drone effects, and narrative philosophical monologues. In Zheruyik, polyphonic techniques and indigenous instruments enrich the leitmotivic development of the singer-prophet. The research highlights the foundational role of epic tradition in shaping a distinctive national operatic language and proposes directions for future innovative explorations of recitative in contemporary Kazakh composition. The practical significance lies in enriching opera repertoire and methodological frameworks for music theatres, while the theoretical contribution is a comparative analysis of national and global recitative practices. The article is structured into conceptual, analytical, and synthetic sections, offering a methodological basis for subsequent scholarship and artistic innovation.